1991
DOI: 10.1007/bf00500378
|View full text |Cite
|
Sign up to set email alerts
|

Defects in insulin binding and receptor kinase in cells from a woman with type A insulin resistance and from her family

Abstract: Summary.Defects in insulin receptor function lead to impairment of the insulin response. We treated a patient with the typical phenotype of type A syndrome of insulin resistance whose insulin receptor seemed to lack the transmembrane region and cytoplasmic domain. Hyperinsulinaemia and resistance to exogenous insulin were evident, and insulin binding to cells and uptake of 2-deoxyglucose into fibroblasts were greatly decreased. Molecular weight of the c~-subunit of the insulin receptor was normal, but autophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Patients with acanthosis nigricans show a type A of insulin resistance similar to that in our patient with a decreased binding of insulin [12,30,36,43,60,61] to its receptor. More is known about the insulin receptor and insulin resistance in acanthosis nigricans, which is often found in patients with lipoatrophic diabetes.…”
Section: Pathogenesis Of Insulin Resistancesupporting
confidence: 79%
See 1 more Smart Citation
“…Patients with acanthosis nigricans show a type A of insulin resistance similar to that in our patient with a decreased binding of insulin [12,30,36,43,60,61] to its receptor. More is known about the insulin receptor and insulin resistance in acanthosis nigricans, which is often found in patients with lipoatrophic diabetes.…”
Section: Pathogenesis Of Insulin Resistancesupporting
confidence: 79%
“…Fat tissue has now been determined to be as a target organ for the action of insulin. Reports on decreased insulin binding to its receptor and possible postreceptor defects emphasize the topical interest in this [1,12,21,30,36,43,45,48,[59][60][61]. Reports on decreased insulin binding to its receptor and possible postreceptor defects emphasize the topical interest in this [1,12,21,30,36,43,45,48,[59][60][61].…”
mentioning
confidence: 99%
“…The tyrosine kinase domain of the IR is initially phosphorylated by insulin binding and greatly augmented by insulin-stimulated autophosphorylation (White & Kahn 1994). Various mutations in the IR gene have been identified in human subjects (Taira et al 1989, Shimada et al 1990, Suzuki et al 1991, Tritos & Mantzoros 1998, and some patients with a mutation in the tyrosine kinase domain of the IR b-subunit show hyperinsulinemia and insulin resistance. Alterations in the IR gene result in varying degrees of glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cloning of the normal 12 kb and abnormal 10.8 kb fragments revealed that one allele of the insulin receptor gene inherited from her mother contained a 1.2 kb deletion, including the 14th exon, and that the proband was a heterozygote of the mutant allele. Four other members of her family with the same mutation presented neither acanthosis nigricans nor hirsultism and only the proband was obese [4,5].…”
Section: Patientmentioning
confidence: 98%
“…The structure of this gene has also been characterized [3], it is composed of 22 exons and contains over 100 kilobases (kb). We examined a patient with type A insulin resistance and found evidence for a 1.2 kb deletion in the insulin receptor gene (IR-Yamanashi) [4,5]. Several types of mutations in the insulin receptor genes have been identified in patients with insulin resistance [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%